2020
DOI: 10.1029/2020ea001111
|View full text |Cite
|
Sign up to set email alerts
|

Huntsville Alabama Marx Meter Array 2: Upgrade and Capability

Abstract: The Córdoba Argentina Marx Meter Array (CAMMA), consisting of 10 second-generation Huntsville Alabama Marx Meter Array (HAMMA 2) sensors, operated at Córdoba, Argentina, during the Remote sensing of Electrification, Lightning, And Mesoscale/microscale Processes with Adaptive Ground Observations (RELAMPAGO) field campaign in late 2018. Initial results obtained from the campaign demonstrate that the new sensor is able to provide a significantly more detailed depiction of various lightning processes than its firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Similar fluctuating behavior can also be recognized in the negative leaders mapped by other authors who used low-frequency lightning mapping systems (e.g., Lyu et al, 2016;Zhu et al, 2020).…”
Section: Journal Of Geophysical Research: Atmospheressupporting
confidence: 75%
“…Similar fluctuating behavior can also be recognized in the negative leaders mapped by other authors who used low-frequency lightning mapping systems (e.g., Lyu et al, 2016;Zhu et al, 2020).…”
Section: Journal Of Geophysical Research: Atmospheressupporting
confidence: 75%
“…In addition, a recent study showed that a VHF lightning mapping system located a smaller number of sources than an LF/MF lightning mapping system, especially for those sources occurring in the negative charge layer at a low altitude (Zhu et al., 2020). A longer time window length by using the VHF lightning mapping system (80 μs) than that of the LF/MF lightning mapping system (30 μs) was speculated to be one of the factors that caused the difference.…”
Section: Methodsmentioning
confidence: 99%
“…This means that the VHF radiation sources located by our network in the negative charge layer may be slightly less than that which could be located by the VHF lightning mapping system mentioned above. However, the short baseline of our network (Figure 1 in Wang et al., 2018) is advantageous for the capability of detecting more VHF radiation sources (Zhu et al., 2020). On the whole, the comprehensive effect of the network layout and parameter settings on the existing detection efficiency may not be significant.…”
Section: Methodsmentioning
confidence: 99%
“…The CAMMA consists of 10 electric field change sensors deployed in an array with 30-60 km baselines near Córdoba in central Argentina for the Remote sensing of Electrification, Lightning, And Mesoscale/ microscale Processes with Adaptive Ground Observations (RELAMPAGO) field campaign. Each sensor has two channels, a fast channel with a decay time constant of 100 µs, which is used for lightning mapping, and a slow channel with a decay time constant of 100 ms for charge retrieval analysis (Zhu et al, 2020b). Only the fast-channel waveforms were used for training the model in this study because the fast channel can detect small-amplitude pulses, and thus can provide pulses with a full range of amplitudes for model training.…”
Section: Cordoba Marx Meter Arraymentioning
confidence: 99%
“…Only the largest peak in each 800-µs window was used for locating. Note that the 800-µs window is much longer than the 30-µs window used in other techniques that can depict lightning development in detail (Zhu et al, 2020a(Zhu et al, , 2020b, but it allows fast processing of a large amount of data while also provide enough data for model training. The CAMMA requires a minimum of six stations to locate a lightning source.…”
Section: Cordoba Marx Meter Arraymentioning
confidence: 99%